1996
DOI: 10.1093/geront/36.5.694
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Elder Abuse and Substance Abuse in the Illinois Elder Abuse System

Abstract: This article explores the role of abuser substance abuse in 552 cases of substantiated elder abuse in Illinois. When the abuser was identified as having a substance abuse (SA) problem, the type of elder abuse substantiated was more likely to involve either physical or emotional abuse than neglect or financial exploitation. Abusers with SA problems were more frequently men and children of their victims, and less likely to be caregivers. Abuser SA was associated with victim SA. Cases involving abusers with SA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
2
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 13 publications
3
48
2
1
Order By: Relevance
“…Studies also associate physical abuse and chronic verbal aggression with spouses rather than with more distant contacts (9,23), and associate financial abuse with distant relatives and nonrelatives (9). Likewise, studies associate physical and emotional abuse with caregiver substance abuse (24) and physical abuse with caregiver alcohol abuse (22). In addition, another study related caregiver substance abuse to care receiver substance abuse (24).…”
Section: Correlatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also associate physical abuse and chronic verbal aggression with spouses rather than with more distant contacts (9,23), and associate financial abuse with distant relatives and nonrelatives (9). Likewise, studies associate physical and emotional abuse with caregiver substance abuse (24) and physical abuse with caregiver alcohol abuse (22). In addition, another study related caregiver substance abuse to care receiver substance abuse (24).…”
Section: Correlatesmentioning
confidence: 99%
“…Likewise, studies associate physical and emotional abuse with caregiver substance abuse (24) and physical abuse with caregiver alcohol abuse (22). In addition, another study related caregiver substance abuse to care receiver substance abuse (24). Studies in dementia report an association of physical abuse with higher caregiver burden scores (25), depression scores (25,26), general health symptom scores (27), and longer duration of caregiving (25).…”
Section: Correlatesmentioning
confidence: 99%
“…62 Tatara's study of abuse across 18 states also found that family members were the suspected abusers in two-thirds of the cases. 63 Various characteristics of the abusing individual that have been found to be associated with abuse of an elder in a home setting, include advanced age, 64 alcoholism, 65 intellectual de cits, 66 inadequate communication skills, 67 substance abuse, 68 depression, 69 poor physical health, 70 stress, 71 social isolation, 72 nancial dif culties, 73 and dependence on the elderly individual. 74 Individuals also may be more likely to abuse the elder if they are limited in their understandin g of the elder's physical and emotional needs 75 or if they have LOUE unrealistic expectations about the elder's abilities or the likelihood of a favorable prognosis.…”
Section: Risk Factors For Elder Abuse and Neglectmentioning
confidence: 99%
“…Substance abuse by a caregiver was more likely to involve physical and emotional abuse (Hwalek, Neale, Goodrich, & Quinn, 1996). When compared with elder sexual abuse victims reported to the criminal justice system (CJS), sexual abuse victims reported to APS were more likely to be abused at home (Burgess, RamseyKlawsnik, & Gregorian, 2008).…”
Section: Categories Of Studies Characteristics Associated With Abuse mentioning
confidence: 99%
“…Both groups involved primarily offspring who resided with their victims but did not have guardianship over them. Looking at over 500 Illinois cases, Hwalek et al (1996) compared substance abusers with other perpetrators and found that substance abusers more frequently physically or emotionally abused, rather than neglected or financially exploited their victims. Social workers rated cases with substance abusing perpetrators as at higher risk for continued abuse than other cases.…”
Section: Characteristics Of Alleged Perpetratorsmentioning
confidence: 99%